Anatomical Variations of Hepatic Arterial Anatomy on Abdominal Computed Tomography in over 300 Scans - Aljiffry, Murad M.; Alhazmi, Mohammed F. (Journal of King Abdulaziz University: Medical Sciences, 2023)
Abstract: Aim: Identifying anatomical variations in the hepatic artery is crucial before performing surgical or radiological interventions to avoid damaging abnormal, replaced, or uncommon arterial supplies. Our study measured the occurrence of hepatic arterial anatomical variations in a local population using computed tomography (CT). Materials and Methods: We analyzed all abdominal CT studies with intravenous contrast conducted at King Abdulaziz University Hospital over one fiscal year. The study included 351 studies. Michel’s and Hiatt’s classification systems were adopted to describe the variations. Results: In our study of 351 abdominal CT scans, we discovered that the accessory left hepatic artery (Type V) was the most prevalent abnormal variation based on Michel’s classification, occurring in 13.1% of cases. Hiatt’s classification identified the replaced or accessory left hepatic artery (Type II) as the most common abnormality, occurring in 19.1% of cases. Other variations were observed. Conclusion: Our study highlights the significance of hepatic artery variations in liver surgery and interventional radiology, such as the presence of accessory left hepatic artery and replaced hepatic arteries. Understanding these variations is crucial for optimizing patient care and improving outcomes in various clinical scenarios. Ongoing research is crucial for advancing this field.